2017
DOI: 10.1115/1.4034994
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Strain as a Predictor of Impact-Induced Fissuring in Articular Cartilage

Abstract: Mechanical damage is central to both initiation and progression of osteoarthritis (OA). However, specific causal links between mechanics and cartilage damage are incompletely understood, which results in an inability to predict failure. The lack of understanding is primarily due to the difficulty in simultaneously resolving the high rates and small length scales relevant to the problem and in correlating such measurements to the resulting fissures. This study leveraged microscopy and high-speed imaging to reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
9
1
Order By: Relevance
“…Our procedure, based on integrating accelerating data, was sensitive to the selected integration boundaries and may be not sufficiently reliable to calculate displacements. However, given the highly heterogeneous axial strain field through the thickness of cartilage under compression, bulk strain is likely not a good predictor of local damage 46 , possibly explaining the lack of correlate that we report.…”
Section: Limitations and Outlookcontrasting
confidence: 64%
“…Our procedure, based on integrating accelerating data, was sensitive to the selected integration boundaries and may be not sufficiently reliable to calculate displacements. However, given the highly heterogeneous axial strain field through the thickness of cartilage under compression, bulk strain is likely not a good predictor of local damage 46 , possibly explaining the lack of correlate that we report.…”
Section: Limitations and Outlookcontrasting
confidence: 64%
“…Failure levels for contact pressure, tensile strain, shear stress, and fluid pressure in articular cartilage and labrum vary widely based on many factors including the health, hydration, or thickness of the cartilage; the loading rate or strain rate; and the joint in question [15,18,29,48]. Thus, it is difficult to indicate the direct physical interpretation for the magnitude of the variables in this study (such as, cartilage will rupture, become damaged, or degraded, etc.).…”
Section: Quantitative Interpretation Of Resultsmentioning
confidence: 99%
“…Large crack lengths and severe damage to microstructural features were induced under relatively high-frequency compressive loading 30 , 31 . Recently, the authors and others found that impact loading, simulating the onset of post-traumatic OA, caused fissures and cracks 32 34 and that crack nucleation in cartilage was largely rate-dependent 35 , 36 . In particular, the authors observed that the solid matrix around the crack surfaces underwent larger relaxation and rearrangement at the slow loading rate compared to the fast loading rate 36 .…”
Section: Introductionmentioning
confidence: 99%